2017
DOI: 10.3389/fpls.2017.00825
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Over-Fertilization and Nutrient Misbalance of Irrigated Tomato Crops in Brazil

Abstract: Over the past 20 years, the use of center-pivot irrigation has increased tomato (Solanum lycopersicum L.) yields in Brazil from 42 Mg ha−1 to more than 80 Mg ha−1. In the absence of field trials to support fertilizer recommendations, substantial amounts of phosphorus (P) have been applied to crops. Additional P dosing has been based on an equilibrated nutrient P budget adjusted for low-P fertilizer-use efficiency in high-P fixing tropical soils. To document nutrient requirements and prevent over-fertilization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 35 publications
2
40
0
1
Order By: Relevance
“…The results showed that increasing the concentration of P until 175 ppm or 200 ppm starting at 12 and 13 WAT have a number of flowers was formed. This data in line with Nowaki et al (2017) who found that the optimum P can increase some of the reproductive properties of the plants in the form of total mass of flowers, fruit production, and number of seed production of pollen per plant. Phosphorus plays a role in increasing the photosynthetic reaction in plants (Gad & Kandil, 2010).…”
Section: Number Of Flowerssupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed that increasing the concentration of P until 175 ppm or 200 ppm starting at 12 and 13 WAT have a number of flowers was formed. This data in line with Nowaki et al (2017) who found that the optimum P can increase some of the reproductive properties of the plants in the form of total mass of flowers, fruit production, and number of seed production of pollen per plant. Phosphorus plays a role in increasing the photosynthetic reaction in plants (Gad & Kandil, 2010).…”
Section: Number Of Flowerssupporting
confidence: 89%
“…Application of phosphorus starting from 175 ppm significantly increased Harvest Index and the concentration of phosphorus 200 ppm showed the highest Harvest Index (Table 4). According to Nowaki et al (2017) that the lower the concentration of P applied on tomato plants lead to a decrease on plants dry weight in general so that the lower plants dry weight produced mainly fruit, resulting lower harvest index values.…”
Section: Harvest Indexmentioning
confidence: 99%
“…This result suggests that the hybrid Heinz has greater efficiency in the use of NPK fertilizers. However, Nowaki et al (2017) found no difference between the yields of tomato plants working with P in areas of high and low fertility in São Paulo state, Brazil, and these authors point out the need for balanced management of nutrients during tomato cultivation.…”
Section: Resultsmentioning
confidence: 82%
“…The nitrogen is cited as one of the main nutrients for tomato, because it constitutes organic compounds that are vital to plants and contributes to fruiting, productivity and economic profitability, but can decrease fruit firmness (Marschner, 2012). Despite being absorbed in smaller quantity and having lower concentrations in plant tissue, the phosphorus is extremely important in root formation and growth, besides increasing the commercial quality of the fruit (Mueller et al, 2013;Nowaki et al, 2017). The potassium is the most required nutrient by tomato (Prado et al, 2011) and contributes to the processes of photosynthesis, enzymatic activation and protein synthesis (Rebouças Neto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The P fixation by oxy-hydroxides of Fe and Al at low pH values reduces P fertilizer-use efficiency in the acidic P-fixing podzolic soils used for lowbush blueberry production [ 76 ]. However, making P fertilizer application based on soil P fixing capacity alone can result in wrong decisions [ 77 ]. Soil pH values exceeding 5.2 can decrease the yield of lowbush blueberry [ 73 ].…”
Section: Discussionmentioning
confidence: 99%